Treatment of a fine soil of high plasticity with mineral coal bottom ash activated with cement, for use as a road subgrade - Shuan Lucas, Luisa Esther (2024)
The current trend in soil stabilization involves the application of sustainable alternatives utilizing local materials. This study proposes the treatment of high plasticity fine soil sourced from Cajamarca, Perú, using mineral coal bottom ash (BA) and cement. The soil was classified as A-7-5 (27) of the AASHTO system, has low-quality as a subgrade, with a CBR 2.0% that does not meet resistance specifications. With the addition of BA, an improvement in the geotechnical properties was evidenced by a  reduction in plasticity and fines content, however, the CBR only increased from 2.0%  to 2.4% with 30% BA content. To enhance the effectiveness of BA, Type I Portland cement  was incorporated at dosages of 1.0%, 1.5%, 2%, and 4.0%, the results were satisfactory,  CBR values exceeded the required minimum. In a soil sample  with 1% cement and 30% BA,  CBR 14.1%  was obtained. With 1.5% cement and BA between 10%  and 30% the CBR increased ranging 13.7% to 72% respectively. This study concludes that the addition of a small quantity of cement significantly impacts the pozzolanic reaction, and the CBR increases according to the BA content.